Pengaruh Pijat Perineum dalam Mengurangi Ruptur Perineum saat Persalinan - Nurhamida Fithri; Lasria Simamora (LPPM STIKES Guna Bangsa, 2022)
A tear in the perineum is one of the various complications during labor in the second stage so it can cause reproductive organ dysfunction in women. Tension in the pelvic floor muscles often results in perineal tears, especially in primigravida. One way to reduce perineal tears is to perform perineal massage to increase blood flow and perineal elasticity through a very simple and short method. There are 2.7 million cases of perineal tears in childbirth and is estimated to increase by 6.3 million in 2050. In Asia, perineal ruptures account for 50% of perineal ruptures in the world. In Indonesia, mothers who experience perineal rupture at the age of 32-39 years are 62%. Research at the Benin Teaching Hospital, Nigeria, showed that the prevalence of perineal rupture was approximately 46.6%, especially in primigravida mothers who experienced perineal rupture. The purpose of this study was to determine the effect of perineal massage in reducing perineal rupture at the time of delivery. This research method is an experiment using a post-test-only control group design. The population in this study were all primiparous pregnant women in the third trimester who visited Mahanum clinic, while the number of samples was 32 samples with two groups, namely the intervention group and the control group. From the results of the analysis, the value of OR = 6.72 means that primiparous pregnant women who do not have perineal massage have a 6.72 times chance of perineal rupture compared to primiparous pregnant women who do perineal massage.